GAYA BAHASA PUISI “PEREMPUAN YANG TERGUSUR” KARYA W.S. RENDRA (STYLISTICS OF POETRY “PEREMPUAN YANG TERGUSUR” BY W.S. RENDRA) - Titik Wijanarti (Kadera Bahasa, 2016)
Words in poetry bear powers to deliver meaning to the reader. This research analyzes a work of Rendra, entitled “Perempuan yang Tergusur” (Side-washed Woman.) Rendra was known as a poet who wrote poems in the nuance of protest and social critic. The problem of this research is how Rendra made use of stylistica in the poem to stylistics in the poem to voice social critic to the reality. Methods and theoretical basis made use in the research is stylistics. Based on the conducted analysis, it resulted that Rendra made use of the means of rhetoric, such as imagery, to describe the problem shown it the poem.